2010
DOI: 10.1097/sih.0b013e3181e98b29
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Simulation Versus Traditional Tutorial-Based Training on Physiologic Stress Levels Among Clinicians: A Pilot Study

Abstract: After high-fidelity SBT within the gastroenterology suite, clinicians independent of their role demonstrated increased physiologic stress levels-as measured by HR and SC levels-compared with traditional IET sessions. The study provides novel calibration data compared with a traditional baseline for future investigations aimed at further understanding the dose-response curve of simulation-based experiences to optimize emotionality, cognition, and learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 13 publications
7
54
0
2
Order By: Relevance
“…A growing number of studies have reported that simulated scenarios may provoke substantial acute stress in doctors, nurses and other allied professionals 7 - 10 , 34 - 36 . Some authors have suggested that the potential of a simulated scenario to induce acute stress in learners may be an indicator of realism, fidelity and engagement, 15 , 16 especially in regards to what some authors have defined as psychological, 20 phenomenal 19 or high emotional and experiential fidelity 17 …”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have reported that simulated scenarios may provoke substantial acute stress in doctors, nurses and other allied professionals 7 - 10 , 34 - 36 . Some authors have suggested that the potential of a simulated scenario to induce acute stress in learners may be an indicator of realism, fidelity and engagement, 15 , 16 especially in regards to what some authors have defined as psychological, 20 phenomenal 19 or high emotional and experiential fidelity 17 …”
Section: Discussionmentioning
confidence: 99%
“…Commentators have also advocated using techniques such as functional magnetic resonance imaging 32 and eye tracking, 33 but these research areas are in their infancy and applications to the physically active learning environments in healthcare simulation will be challenging. Simulation researchers have also measured salivary cortisol 34 and heart rate variability as markers of stress, but the complex relationship between stress and cognitive load is not completely understood (see later); further research into the best physiologic markers for each is needed.…”
Section: Intrinsic Cognitive Loadmentioning
confidence: 98%
“…However, there were also some indications of drawbacks, which include high levels of anxiety and stress [20,21]. Although little is known about which personal and contextual factors facilitate or impair transfer of learning from a simulation based setting to the clinical setting, it is thought to be important to provide feedback early on in order to support optimal performance [22].…”
Section: Discussionmentioning
confidence: 99%